2016
DOI: 10.18632/oncotarget.7944
|View full text |Cite
|
Sign up to set email alerts
|

A combination of trastuzumab and BAG-1 inhibition synergistically targets HER2 positive breast cancer cells

Abstract: Treatment of HER2+ breast cancer with trastuzumab is effective and combination anti-HER2 therapies have demonstrated benefit over monotherapy in the neoadjuvant and metastatic settings. This study investigated the therapeutic potential of targeting the BAG-1 protein co-chaperone in trastuzumab-responsive or -resistant cells. In the METABRIC dataset, BAG-1 mRNA was significantly elevated in HER2+ breast tumors and predicted overall survival in a multivariate analysis (HR = 0.81; p = 0.022). In a breast cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Sixteen studies utilised cohorts of 100 or more patients ( Tang et al , 1999 ; Turner et al , 2001 ; Townsend et al , 2002 ; Cutress et al , 2003 ; O’Driscoll et al , 2003 ; Sirvent et al , 2004 ; Tang et al , 2004 ; Yun et al , 2005 ; Lin et al , 2008 ; Nadler et al , 2008 ; Millar et al , 2009 ; Afentakis et al , 2013 ; Wang et al , 2014 ; Dowsett et al , 2015 ; Davidson et al , 2016 ; Papadakis et al , 2016 ) and 2 studies ( Yang et al , 2008 ; Athanassiadou et al , 2009 ) recruited <100 patients. With the exception of one prospective immunocytochemical study ( Athanassiadou et al , 2009 ), and two retrospective analyses of a prospective clinical trial ( Afentakis et al , 2013 ; Dowsett et al , 2015 ), the studies associating BAG-1 expression with clinicopathological variables involve retrospective analysis of patient survival data ( Table 2a and b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies utilised cohorts of 100 or more patients ( Tang et al , 1999 ; Turner et al , 2001 ; Townsend et al , 2002 ; Cutress et al , 2003 ; O’Driscoll et al , 2003 ; Sirvent et al , 2004 ; Tang et al , 2004 ; Yun et al , 2005 ; Lin et al , 2008 ; Nadler et al , 2008 ; Millar et al , 2009 ; Afentakis et al , 2013 ; Wang et al , 2014 ; Dowsett et al , 2015 ; Davidson et al , 2016 ; Papadakis et al , 2016 ) and 2 studies ( Yang et al , 2008 ; Athanassiadou et al , 2009 ) recruited <100 patients. With the exception of one prospective immunocytochemical study ( Athanassiadou et al , 2009 ), and two retrospective analyses of a prospective clinical trial ( Afentakis et al , 2013 ; Dowsett et al , 2015 ), the studies associating BAG-1 expression with clinicopathological variables involve retrospective analysis of patient survival data ( Table 2a and b ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported analysis of mRNA expression from published data sets: Millar et al (2009) from two studies ( van de Vijver et al , 2002 ; Naderi et al , 2007 ) and Papadakis et al (2016) from a third ( Curtis et al , 2012 ). Of the 18 studies, all clearly stated inclusion and/or exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2-associated athanogene 1 (BAG-1) is a multifunctional protein that interacts with a wide range of molecules and subsequently affects various cellular functions (5)(6)(7)(8)(9)(10). BAG-1 protects cells from apoptosis otherwise induced by treatment with cytotoxic drugs, growth factor withdrawal, radiation and stress (11)(12)(13)(14)(15). BAG-1 is expressed in three main isoforms, which differ in their translation initiation starting positions (16,17).…”
Section: Downregulation Of Bag-1 In T47d Cells Promotes Resistance Tomentioning
confidence: 99%
“…Papadakis et al 2 state ‘In general, data were too heterogeneous, and outcome measures were too varied to perform meta-analyses for the majority of studies. Meta-analyses of mRNA expression from the two data sets analysed in Millar et al 7 and the data set analysed in Papadakis et al 11 including a total of 2422 patients produced an HR of 0.55 (95% CI: 0.36–0.85) favouring improved BCSS with high expression of BAG-1 (Figure 2a in Papadakis et al 2 ).’ The first sentence implies that a sensible meta-analysis is not possible, an unfortunate situation seen in many systematic reviews of prognostic biomarkers. Nevertheless, Papadakis et al 2 conducted three meta-analyses summarising two or three studies.…”
Section: Meta-analysismentioning
confidence: 96%